Aminosilicate sol-gel stabilized N-doped TiO2-Au nanocomposite materials and their potential environmental remediation applications - Pandikumar, Alagarsamy; Sivaranjani, Kumarsrinivasan; Gopinath, Chinnakonda S.; Ramaraj, Ramasamy (RSC Advances, 2013)
A facile chemical reduction method to synthesize amine functionalized silicate sol-gel-supported gold-deposited nitrogen-doped Degussa-TiO2 nanocomposite materials (APS/(N-P25-Au)(NCM)) is reported and the materials are characterized by DRS, PL, XRD, TEM, Raman, XPS and BET surface area analysis. The application of the synthesized APS/(N-P25-Au)(N)CM towards environmental remediation processes are investigated by studying the catalytic oxidation of carbon monoxide (CO) and photocatalytic reduction of toxic mercuric (Hg(II)) ions. The catalytic and photocatalytic activity of the prepared catalysts are found to be in the order of APS/(N-P25-Au)(NCM) >> APS/(P25-Au)(NCM) > N-P25 > P25. The enhanced catalytic and photocatalytic activities of the APS/(N-P25-Au)(NCM) can be attributed to the synergistic effect of Au-nps and N-doped P25. The catalytic activities of the APS/(N-P25-Au)(NCM) are very promising in the field of green technology for the environmental cleaning applications.